2003
DOI: 10.1046/j.1365-2591.2003.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of gutta‐percha from root canals using an Nd:YAG laser

Abstract: Use of an Nd:YAG laser alone is capable of softening gutta-percha. The addition of solvents did not improve the retreatment, either in terms of the time required for the procedure or in terms of the area of remaining gutta-percha on root-canal walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 17 publications
(25 reference statements)
2
41
0
3
Order By: Relevance
“…[4] Various techniques have been advocated to remove obturating materials from the root canal system during retreatment. [567] The ProTaper Universal Retreatment system consists of three retreatment files, D1, D2 and D3, which are designed to be used in the coronal, middle and apical third of the root canal respectively. The triangular cross section of these instruments is similar to the ProTaper shaping and finishing files.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Various techniques have been advocated to remove obturating materials from the root canal system during retreatment. [567] The ProTaper Universal Retreatment system consists of three retreatment files, D1, D2 and D3, which are designed to be used in the coronal, middle and apical third of the root canal respectively. The triangular cross section of these instruments is similar to the ProTaper shaping and finishing files.…”
Section: Introductionmentioning
confidence: 99%
“…These include endodontic hand files combined with heat or chemical solvents, engine-driven rotary files, ultrasonic instruments, heat-carrying instruments, paper points with chemicals, and lasers (7,8). Two nickel-titanium (NiTi) systems have recently introduced rotary instruments specifically designed for removing semisolid filling materials: the Mtwo R (retreatment) rotary files (Sweden & Martina, Padova, Italy) and the ProTaper Universal retreatment files (Dentsply-Maillefer, Ballaigues, Switzerland).…”
mentioning
confidence: 99%
“…20 Interestingly studies by Viducic, Jukic showed that the use of Nd:YAG laser alone is capable of softening gutta-percha and addition of solvents did not improve retreatment, either in terms of time required for procedure or in terms of area of remaining gutta-percha on root canal walls. 21 Literature shows conflicting reports about the efficacy of Nd:YAG laser in removal of smear layer. Aric, Taclubara studied the effect of Nd:YAG, CO 2 and argon lasers and observed that there was statistically significant difference in permeability between lased groups with and without a smear layer in the cervical third of the root canal following lasing, while in the middle third all three laser types induced permeability increase in groups with a smear layer.…”
Section: 5005/jp-journals-10022-1036mentioning
confidence: 99%